ISLAMIC FINANCIAL PLANNING: KONSEP LITERASI KEUANGAN SYARIAH SEBAGAI ALTERNATIF PERENCANAAN FINANSIAL BAGI MAHASISWA - Muhamad Parhan; Muhammad Abyan Ashshidqi; Lia Sylvia Dewi; Sherly Lorenza Bunga Edelweis; Fitri Regina Prayoga; Anwar Taufik Rakhmat Taufik Rakhmat (Universitas Muhammadiyah Prof Dr Hamka, 2022)
In this modern era, financial literacy is one of the most important substance. Financial literacy is an alternative strategy to building economic growth and financial stability to survive and face the diversity of services available. The concept of Islamic finance is managing finances better, and being smart for choosing halal and profitable investments. The role of students regarding the level of sharia literacy is needed to disseminate it to the community which will ultimately be implemented by the community itself. Improving financial literacy must be a program at every university for all students because the role of financial regulation, according to sharia is very important for a good level financial literacy. This study uses a qualitative research method with a descriptive approach. The technique used to collect data in this research is a questionnaire. The population of this research is Indonesian Muslim's students by using purposive sampling technique. The results show that most Indonesian Muslim students have some problems in managing finances. This happens because of the lack of socialization related to Islamic Financial Planning so that students find it difficult to apply it in everyday life. There needs to be long-term socialization so that students can understand it well. Keywords; Islamic Financial Literacy; Islamic Financial Planning; Student Finance